Adverbs of Time in Arabic and English: Comparative Study - Mehdi, Mohamed Farhat; Jaradat, Mazen (International Journal of Linguistics, 2021)
Adverbs are words that are used to change, modify or qualify several types of other words including adjectives, verbs, or other adverbs. There are five basic types of adverbs in the English language, namely that of Manner, Time, Place, Frequency, and Degree. In the Arabic language, there are just two adverbs namely that of Time and Place. This research aimed to prove that the adverb of time exists in both Arabic and English languages and to compare and state the similarities and differences between the two languages. Most importantly, to show which were more the similarities or the differences? The results showed that the similarities were more than the differences despite the fact that the two languages are not from the same family.